Factors Related to Adolescent Knowledge About HIV-AIDS Prevention in Students Madrasah Aliyah Negeri Pematangsiantar - Efrin; Damanik, Debby Seprianti (PT Inovasi Pratama Internasional, 2023)
Human Immunodeficiency Virus (HIV) and Acguired Immune Deficiency Syndrome (AIDS) have become serious health problems in the 20th century. HIV-AIDS in adolescents needs attention. The highest proportion of AIDS was in the age group of 20-29 years (47.2 % ), the at-risk group of adolescents, aged 15-18 years, is a group that is vulnerable to STIs (Sexually Transmitted Infections) with the largest number of people living with HIV-AIDS. National statistical data on HIV-AIDS sufferers in Indonesia, aged 15-24 years contribute 40% of all new HIV infections, every day more than 2500 teenagers are infected and more than 5.7 million teenagers are living with HIV-AIDS. There were 476 people living with HIV who were registered. This type of research is a cross-sectional survey research design. And the results of this study stated that there was a significant relationship between information sources, living environment, and age with adolescent knowledge about HIV-AIDS prevention with a chi-sguare p value = 0.000. The most widely used information source was electronic media of 53, 8 %. Residential environment, 64.8 % of respondents live with their parents. The majority of respondents are aged 13-15 years, namely 56% and those who have a good level of knowledge are 23.1 % . Based on the regression analysis, it was stated that information sources contributed to knowledge by 10.6 % , living environment contributed to knowledge by 11.9%, age contributed to knowledge by 27.9%. And the most dominant contribution to knowledge is age, which is equal to 27.9 %.